2019
DOI: 10.1021/acscatal.9b01001
|View full text |Cite
|
Sign up to set email alerts
|

Mott–Schottky Effect Leads to Alkyne Semihydrogenation over Pd-Nanocube@N-Doped Carbon

Abstract: Improving the selectivity and retaining the efficiency of catalysts are essential for industrial processes and remain a great challenge. Herein, we developed a facile route to synthesize Pd nanocubes (NCs) using Eosin Y as the photosensitizer under visible light. Subsequently, Pd NCs were uniformly loaded on N-doped carbon nanofibrous microspheres (NCMs) from carbonated chitin microspheres. This Pd NCs@NCM exhibited high reactivity and selectivity in alkyne semihydrogenation. For example, the hydrogenations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 72 publications
0
68
0
Order By: Relevance
“…Besides, the C 1s peaks in HPCM‐5 exhibits a slight shift to lower one compared to MPCM (Figure 2e). These results further indicated that electrons transfer from Fe to N doped graphitic C at the heterojunction interfaces 6,9a,10,18. Overall, the charge regulation by Mott–Schottky effect in HPCM‐5 effectively causes electrons redistribution, forming a fast electron transfer path and enhancing ORR performance, which will be further discussed latter.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Besides, the C 1s peaks in HPCM‐5 exhibits a slight shift to lower one compared to MPCM (Figure 2e). These results further indicated that electrons transfer from Fe to N doped graphitic C at the heterojunction interfaces 6,9a,10,18. Overall, the charge regulation by Mott–Schottky effect in HPCM‐5 effectively causes electrons redistribution, forming a fast electron transfer path and enhancing ORR performance, which will be further discussed latter.…”
Section: Resultsmentioning
confidence: 68%
“…N heteroatom‐doping in carbon can change the charge or spin distribution, which is beneficial to facilitate the O 2 adsorption and then improve the ORR performance 16. What is more, N doping could open the band gap of C by raising the conduction band bottom and lowering the valence band top 3h,9,10. The introduced N atoms are mainly pyridinic‐N (398.6 eV) and graphitic‐N (401.1 eV) in HPCM‐5, as revealed by the N 1s high‐resolution spectra (Figure 2d).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, it was found that the metal‐free frustrated Lewis pairs (FLPs) are also highly selective for alkene production . However, the high selectivity of alkenes, especially for the terminal alkenes, was resulted from strict control over the reaction time, because most of the reported semihydrogenation catalysts are also active in alkene hydrogenation reaction …”
Section: Introductionmentioning
confidence: 99%